Community Participation Factors in Implementing Dengue Fever Symptoms Prevention Program - Rosari Inriani S; Juanita Juanita; Lita Sri Andayani (Randwick International of Social Science Journal, 2023)
Dengue Hemorrhagic Fever is one of the most common health problems in society that causes various health problems. This disease is caused by the bite of the Aedes Aegypti mosquito which transmits the dengue virus. Deli Serdang Regency is the district with the highest Dengue Haemoragic Fever (DHF) coverage with a coverage of 1,336 cases. The highest coverage was in Tanjung Morawa sub-district with 154 cases, as well as making Tanjung Morawa Health Center the highest DHF coverage with 92 cases. This think about points to decide the factors that influence community participation in the implementation of the Dengue Fever prevention program at Tanjung Morawa Community Health Center, Deli Serdang Regency. This investigate may be a quantitative explanatory overview investigate with a cross sectional design. The sample used was 270 people with the sampling technique using Proportional Random Sampling. Data analysis used univariate and bivariate analysis. The results showed that the related variable was a source of information (p=0.027) with community participation in the implementation of DHF prevention. While knowledge (p=0.705), attitude (p=0.057), role of stakeholders (p=0.787) are variables that are not related to community participation in the implementation of DHF prevention. Suggestions for this research are that health workers at Tanjung Morawa Health Center can increase the positive reaction of the community to prevent DHF, by conducting home visits to provide clear education about DHF prevention programs, providing periodic larvae inspection visits and inviting every household to have One JUMANTIK every household to prevent and eradicate both mosquito breeding sites and the presence of Aedes aegypti mosquitoes, provide information to the public in the form of counseling about 3Mplus, and how to prevent DHF, and urge the public to participate and report if any neighbors or families are infected with DHF.